Effect of Curcuma longa powder on growth performance, haematological and microbiological parameters of cockerels - Oyebanji, B.O.; Ogunbawo, A.R.; Odiai, G.O.; Abdulazeez, A.A.; Abdulazeez, A.A (Nigerian Journal of Animal Science, 2023)
This study was conducted to assess the effect of Curcuma longa on growth performance, hematological and microbiological parameters of cockerels. A total of one hundred and eighty (180) cockerels with an average weight of 250±0.50g were randomized into six treatment groups. Each treatment group comprised of ten birds per replicate and was replicated three times. Treatment 1 (T1) (250 mg turmeric/kg of feed + coconut oil), treatment 2 (500 mg turmeric/kg of feed + coconut oil), treatment 3 (250 mg turmeric/kg of feed), treatment 4 (500 mg turmeric/kg of feed), treatment 5 (control), treatment 6 (500 mg turmeric/kg of feed + Vitamin C).Weekly body weight and daily feed intake of the birds were recorded for 7 weeks, after which carcass analysis was carried out. At the end of seven weeks, blood samples from ten birds per treatment were collected for haematology and serum biochemical parameters after which six chickens were humanely sacrificed for carcass analysis. Samples of ingesta were collected from crop and ileum and analyzed for lactobacillus counts. There was significant difference (p<0.05) in the average weight gain of birds with birds in treatment 2 having the highest weight gain. In all carcass parameters, there was no significant difference among the treatments. The packed cell volume (PCV) of birds in T1 group (27.00±0.45%) was significantly highest when compared with birds in other treatments. The serum total protein and albumin of birds in groups T4 (7.860±0.15g/dl) and T6 (7.880±0.36g/dl) were significantly (p<0.05) highest compared to other groups. There was no significant difference in the lactobacillus counts in the crop while birds in T2 group had the highest (2.68±0.21 CFU/ml) lactobacillus counts. It can be concluded that Curcuma longa fed to cockerels have no deleterious effect and can be included in their feed up 500 mg/kg of feed with or without coconut oil.